Action mechanism of five microorganism promoters of plan growth - González F., Harold; Fuentes M., Natalia (Revista de Ciencias Agrícolas, 2017)
The indiscriminate use of agrochemicals to increase crop productivity is not an environmentally friendly practice. As a strategy to replace the use of agricultural chemicals, we propose the use of bioinoculation of plant growth-promoting microorganisms. In this context, the objective of this research was to evaluate the effect of five plant growth-promoting microorganism strains on six plants. A fungus (Trichoderma harzianum) and a group of bacteria (Enterobacter aerogenes, Azotobacter sp., Bacillus mycoides and Microbacterium sp.) were selected to evaluate the effect of germination, growth and assimilation in cassava (Manihot esculenta), rice (Oryza sativa), sunflower (Helianthus annuus), peas (Pisum sativum L.), lettuce (Lactuca sativa L.), and papaya (Carica papaya L.). Bioassays included 18 pots per plant species, and each treatment was replicated three, including the control. The inoculum was prepared by seeding 200mL of nutrient broth with an aliquot of each microorganism, then, adding 20mL of inoculum to each pot per treatment. The following variables were evaluated: root number and length, leaves and stems, leaf area, and root and stem biomass. The bioinoculation of Microbacterium sp. and B. mycoides accelerated plant germination regardless of the species. The treatments with Azotobacter sp., T. harzianum and E. aerogenes were not effective in cassava and rice crops. The bioinoculation of Microbacterium sp., B. mycoides and E. aerogenes favored growth, development and yield in rice and pea crops.